EFEKTIVITAS EDUKASI TEKNIK MENYUSUI TERHADAP PENCEGAHAN LECET PUTING PADA IBU NIFAS: STUDI KASUS DI KLINIK PRATAMA JAMBU MAWAR PEKANBARU - Anisa Casandra; Nevi Susianty (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Nipple soreness or abrasions is one of the common problems experienced by breastfeeding mothers and can hinder the success of breastfeeding. One of the main causes of this condition is incorrect breastfeeding technique. This study aims to determine the effectiveness of education on correct breastfeeding techniques in preventing nipple abrasions in Mrs. A at the Pratama Jambu Mawar Clinic. The method used is a case study with a midwifery care approach a qualitative case study. Intervention is carried out through the provision of education on correct breastfeeding techniques, including the positions of the mother and baby, latch-on, and proper baby suction release. Evaluation is conducted through direct observation and interviews after the education is provided. The results showed that after being given education, Mrs. A was able to apply the correct breastfeeding techniques, the baby fed effectively, and no signs of nipple soreness were found. The conclusion of this study is that education on correct breastfeeding techniques is effective in preventing nipple soreness. It is recommended that healthcare workers routinely provide education to breastfeeding mothers to improve the success of breastfeeding